Cardiovascular complications of chemotherapy - Steingo, Leonard (SA Heart Journal, 2017)
Many of the highly effective agents in contemporary oncology, including the anthracyclines and trastuzumab, are known to increase the risk of cardiac events in both the short and long term. As these agents are often used to obtain a cure, the means of maximising their benefits while reducing the risk to the heart has become a priority when managing the patient with a malignancy. In addition, the novel biologic therapies, designed to fulfil unmet needs in oncology, require the development of strategies for risk detection and management that aim to reduce the risk of cardiac toxicity.